Gambaran Kejadian Insomnia Pada Mahasiswa Fakultas Keperawatan Universitas Riau - Rahayu, Venessa; Putri, Syeptri Agiani; Amir, Yufitriana (Innovative: Journal Of Social Science Research, 2024)
Insomnia is a condition where sleep needs are not met in both quantity and quality. According to Chowdhury, et al (2021) insomnia is a sleep disorder characterized by conditions of difficulty falling asleep and staying asleep, waking up in the morning and not being able to fall asleep again, even with adequate opportunities and conditions for sleep. Individuals who experience insomnia feel excessive sleepiness during the day due to insufficient quantity and quality of sleep. This study aims to determine the incidence of insomnia in students of the Faculty of Nursing, Riau University. This research is a quantitative study using a descriptive design with a cross-sectional approach. The research sample was 257 respondents who were taken based on the inclusion criteria using the proportionated stratified random sampling technique. All respondents filled out google forms related to respondent characteristic data and ISI questionnaires. Data were analyzed using univariate analysis and presented in a frequency distribution table. The results of this study showed 60.7% of respondents experienced insomnia with the most sleep problems, namely difficulty falling asleep (74.7%), the majority of respondents were early adulthood (56.8%) and female (89.1%).